2011
DOI: 10.1007/s11255-011-9958-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diabetic nephropathy in subjects with proliferative retinopathy

Abstract: By analysing factors associated with diabetic nephropathy rather than microvascular disease in general, this study provides evidence that night-time diastolic BP and a relative increase in platelet count are associated with incipient diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In support of this hypothesis is the finding that platelet activation is associated with cardiovascular autonomic dysfunction in type 1 diabetic subjects [29] and with sympathetic stimulation in patients with acute myocardial infarction [30]. Interestingly, our group has previously shown that a rise in platelet count is also an independent predictor of diabetic nephropathy in type 2 diabetic subjects [31]. Undoubtedly, further studies are needed to assess the role of platelets in circadian HR rhythm in diabetic patients.…”
Section: Discussionmentioning
confidence: 86%
“…In support of this hypothesis is the finding that platelet activation is associated with cardiovascular autonomic dysfunction in type 1 diabetic subjects [29] and with sympathetic stimulation in patients with acute myocardial infarction [30]. Interestingly, our group has previously shown that a rise in platelet count is also an independent predictor of diabetic nephropathy in type 2 diabetic subjects [31]. Undoubtedly, further studies are needed to assess the role of platelets in circadian HR rhythm in diabetic patients.…”
Section: Discussionmentioning
confidence: 86%
“…Multivariate analysis revealed that nocturnal diastolic BP, platelet count and eGFR were independent predictors of DN development (P=0.002, P=0.018 and P<0.001, respectively) as well as microalbuminuria (P=0.029, P=0.045 and P=0.001, respectively) [49]. Interestingly, retinopathy progressed in all diabetic patients with enough hyperglycemic exposure, in contrast to DN that developed in only a subgroup of diabetic patients, proving that DN is influenced by other factors in addition to hyperglycemic exposure [49]. In conclusion, growing evidence is suggesting that increased nocturnal diastolic BP, nocturnal systolic BP, and/or lower nocturnal BPF might predict the development of micro or macroalbuminuria.…”
Section: Hypertensionmentioning
confidence: 99%
“…The role of HTN is highlighted even more in a recent study of 196 individuals, including 85 with normoalbuminuria, 66 with microalbuminuria, and 45 with macroalbuminuria [49]. Multivariate analysis revealed that nocturnal diastolic BP, platelet count and eGFR were independent predictors of DN development (P=0.002, P=0.018 and P<0.001, respectively) as well as microalbuminuria (P=0.029, P=0.045 and P=0.001, respectively) [49].…”
Section: Hypertensionmentioning
confidence: 99%
“…8–12 A longer duration of diabetes, hypertension, and elevated glycosylated hemoglobin, have been identified as consistent risk factors. 1013 The Early Treatment Diabetic Retinopathy Study group has reported that the type of diabetes, body weight, and the age of the patient are also important risk factors for developing PDR in particular. 8 Risk factors for progression to PDR in particular are of importance, given the risk for severe vision loss in patients with advanced disease.…”
mentioning
confidence: 99%